The Ethical Limits of the Use of Artificial Intelligence for Marketing in the Brazilian Context - Panicachi, Débora Dias; Cohen, Eric David (Anais da Conferência Latino-Americana de Ética em Inteligência Artificial (LAAI-Ethics); 2024: Anais da 1ª Conferência Latino-Americana de Ética em Inteligência Artificial, 2024)
This research explores the perceptions of marketing professionals regarding the use of Artificial Intelligence (AI) in marketing practices within the Brazilian context, focusing on key areas such as product recommendations and market segmentation. A central theme is the ethical boundaries that must guide the application of AI in marketing, particularly in balancing technological advances with consumer expectations. The findings emphasize the importance of ensuring consumer privacy during data collection and managing the risks of information sharing and overload. The paper discusses the limits that should accompany these technological advancements, considering ethical concerns, current legislation, state-of-the-art practices, and regulatory frameworks.